Faktory podílející se na vzniku varikózního krvácení pri portální hypertenzi-- I. cást: bakteriální infekce a porovnání úcinnost intravenózního a perorálního podání antibiotik--randomizovaná studie - Lata, J; Juránková, J; Husová, L; Senkyrík, M; Díte, P; Dastych, M; Príbramská, V (Vnitrni lekarstvi, 2004)
An acute bleeding from oesophageal varices as a result of portal hypertension is a frequent and at the same time serious complication of cirrhosis of the liver. One of factors influencing this bleeding can be a bacterial infection. Endotoxines can increase portal pressure and so participate in development of bleeding and simultaneously deteriorate a patient's prognosis. An antibiotic treatment is a part of a treatment algorithm, however what antibiotics to administer and in what manner is unclear. A group of 46 patients who were admitted to a hospital for an acute bleeding from varices has been compared in the study to 48 cirrhosis patients hospitalised for other reasons. An infection incidence was high in both groups (63.0 % vs. 54.2 %), bleeding patients had more often positive hemoculture (17.3 % vs. 8.6 %), and statistically significantly more often positive findings in throat swab culture (36.9 % vs. 17.3 %, p = 0.04) which is an evidence of an increased pathology colonisation of these patients. Bleeding patients were randomised for peroral norfloxacin administration (n = 25) or an intravenous administration of a combination of ampicilin and sulbactam (n = 21). There was no difference in survival of both groups. Due to a high number of bacterial infections antibiotics administration has been indicated in these patients. Intravenous administration is probably of the same effect as peroral administration.
Keywords: Sulbactam; Aged; Bacterial Infections; aplikace orální; Aged, 80 and over; bakteriální infekce; ampicilin; lidé středního věku; senioři; lidé; ezofageální a žaludeční varixy; Adult; Middle Aged; Administration, Oral; dospělí; Gastrointestinal Hemorrhage; Infusions, Intravenous; jaterní cirhóza; portální hypertenze; Liver Cirrhosis; Female; senioři nad 80 let; Esophageal and Gastric Varices; Anti-Bacterial Agents; Male; ženské pohlaví; Ampicillin; Humans; mužské pohlaví; Hypertension, Portal; norfloxacin; sulbaktam; gastrointestinální krvácení; intravenózní infuze; antibakteriální látky; Norfloxacin